1987
DOI: 10.2307/2232927
|View full text |Cite
|
Sign up to set email alerts
|

Aid, the Public Sector and the Market in Less Developed Countries

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 139.80.123.46 on Mon,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
186
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(205 citation statements)
references
References 8 publications
12
186
0
7
Order By: Relevance
“…dent variable, while P OL is a measure of ethnic and linguistic fractionalization taken from Taylor & Hudson (1972). 25 Because time-series data are not available for the whole period, averaged 1970-89 data is used. As shown in table 4 the results improve considerably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…dent variable, while P OL is a measure of ethnic and linguistic fractionalization taken from Taylor & Hudson (1972). 25 Because time-series data are not available for the whole period, averaged 1970-89 data is used. As shown in table 4 the results improve considerably.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the possibility of simultaneous causality between aid and the¯scal variable was not taken into account. Boone (1994a,b), and to some extent Mosley et al (1987), are exceptions. Conditionality, and particularly macroeconomic conditionality, has emerged as an important component in foreign aid in the 1980s and 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…In the decades that followed, a determined research effort was made to demonstrate the effectiveness of oda in driving growth. Some studies obtained positive results (Levy, 1988), but in others the results were clearly negative (Mosley, Hudson and Horrel, 1987;Mosley, 1980;Boone, 1996). Many of these studies did not treat the endogeneity of oda, which may account for their contradictory results (Arndt, Jones and Tarp, 2010).…”
Section: Official Development Assistance and Economic Growthmentioning
confidence: 99%
“…However, in the mid-1980s, one of the first large-scale empirical studies showed that the data seemed to support Bauer's most unpopular hypothesis (Mosley et al, 1987). Since then, most studies have shown that foreign aid is not robustly associated with economic growth rates as the beneficial effects are either counteracted by adverse political and economic effects or do not arise when foreign aid is used to finance idle government consumption (cf.…”
Section: Introductionmentioning
confidence: 99%